What do people really think of when they claim to believe in repressed memory? Methodological middle ground and applied issues. Issue 6 (3rd July 2022) - Dodier, Olivier; Gilet, Anne-Laure; Colombel, Fabienne
ABSTRACT: What do people really think of when they say they believe in repressed traumatic memory? In two studies ( N Study 1 = 3158; N Study 2 = 305) using an integrative method taking into account recent methodological discussions, we found that, in total, 2458 participants (71% of the two combined samples) reported that they believed in repressed memory. In Study 1, based on separate questions on the whole group, we found 71% of agreement with the concept of repression, 74% with the concept of unconscious repression, and 54% with the concept of deliberate memory suppression. Participants with no memory of childhood abuse endorsed unconscious and deliberate mechanisms less than those with such memories. In Study 2, the order in which the items were presented was not associated with the beliefs in the different statements. Overall, our results show that people see repression as an unconscious mechanism. We suggest the use of within-subject designs and/or follow-up questions to determine how people understand the concept of repression. Such adherence to this controversial concept can have adverse implications in the clinical and legal arenas.